Planos nacionais de educação (2001 e 2014): perspectivas sobre a formação docente continuada - Zuffo, Robledo Leonildo (2018)
The present study investigates the issue of continuing teacher education from the goals and strategies contained in the National Education Plans, edited in 2001 and 2014. The discussions arising from the necessity of teacher training and appreciation are not so recent. However, the National Plans of Education are singular legal/normative instruments, deserving therefore, the academy’s attention and citizen vigilance. To survey the information regarding the development of effective goals and strategies concerning teachers, an analysis of the two National Plans of Education was made: law 10.172, from January 9th, 2001 and law 13.005, from June 25th, 2014. This analysis sought for a better understanding of which concepts and citations on continuing teacher education are present in the two editions of the National Plans. The choice upon this topic was based on its contemporary relevance, besides the expectation to contribute to the academic field. As a result, the study indicates that the topic of continuing teacher education is present in both examined Plans, thus pointing out important paths and tendencies in this scope. Those plans define common goals and strategies concerning continuing teacher education and especially for strengthening the quality of education as a result of an intense process of teaching’ improvement. Finally , it was found that the studied documents allowed to understand that the continuing teacher training must be constant, in order to permeate the daily practice of teaching.